Evaluation of the NDVI as indicator of pasture quality degradation index – an exploratory study in Mediterranean Montado ecosystem - Serrano, João (2020)
Dryland pastures are the principal source of animal feed in extensive animal production systems in the Mediterranean region. The period between the end of Spring (June) and the end of Summer (September) is characterized by a drastic reduction in precipitation and an increase in temperatures, both unfavourable conditions for the development of dryland pastures. The inter-annual irregularity of precipitation can prolong the duration of this critical period of low pasture quality and anticipate the need for animal feed supplementation. The objective of this work was to evaluate two technological approaches to monitor the evolution of the quality of a biodiverse pasture in the period of greatest vegetative development: (i) through proximal sensing (PS), using the NDVI (normalized difference vegetation index) calculated from measurements of an active optical sensor; (ii) through remote sensing (RS), using the NDVI based on satellite images. The following indicators of pasture quality were considered: pasture moisture content (PMC), crude protein (CP), fiber (neutral detergent fiber, NDF) and pasture quality degradation index (PQDI). These were monitored monthly between February and June of three consecutive and representative years (2016, 2017 and 2018). The results of this exploratory study in Portugal showed significant relationships between NDVI (obtained by PS or RS) and all indicators of pasture quality (PMC, CP, NDF and PQDI). This knowledge, that PS and RS can be used in a complementary way to evaluate pasture´s complex response to climatic changes and to identify animal supplementation needs, represents an important contribution to the decision-making process at the level of pasture intensification and dynamic grazing.